Use of vitamin D and infection in patients with chronic kidney disease - Emanuela Cardoso da Silva; Mônica Taminato; Cassiane Dezoti da Fonseca; Graciana Maria de Moraes; Maria Cristina Barbosa Longo; Cibele Esmanhoto Grothe; Angélica Gonçalves Silva Belasco; Dulce Aparecida Barbosa
ABSTRACT Objective: To evaluate the effectiveness of vitamin D supplementation as protection factor against infection of patients with chronic kidney disease on conservative treatment. Method: Retrospective cohort study carried out between 2013 and 2016 in the Conservative Treatment Outpatient Clinics (Ambulatório de Tratamento Conservador) of the Hypertension and Kidney Hospital (Hospital do Rim e Hipertensão) of the Universidade Federal de São Paulo. Data on sociodemographic factors, comorbidity, infection episodes and use or nonuse of vitamin D supplementation for at least 6 months were collected from medical records. The primary outcomes considered in both groups were: presence or absence of infection anywhere on the body (bloodstream, urinary, respiratory and surgical sites). Results: A total of 263 patients were included and those who received (n=43) vitamin D had 59% less chance of developing infections (OR=0.41; 95%CI; 0.15-0.99), when compared to those who did not receive. Conclusion: Vitamin D supplementation was a protective factor against infections of all causes.